HUBUNGAN SELF-EFFICACY DAN DUKUNGAN SOSIAL DENGAN PENYESUAIAN DIRI MAHASISWA SEKOLAH TINGGI ILMU KESEHATAN WIDYA HUSADA MEDAN - Herni Misnita (Jurnal Ilmiah Kebidanan Imelda, 2016)
Basically, this research aims to determine the relationship of self-efficacy and social support student with adjustment College of Health Sciences Widya Husada Medan. The research conducted is quantitative research design, the research subjects students Prodi D III Midwifery many as 61 people. The sampling technique by total sampling and methods used is regression analysis two predictors. The results showed a positive relationship between self-efficacy, with adjustment, with r = 0.441, significance level of 5 %, the relationship between independent variables ( X1 ) with the dependent variable ( Y ) strong and significant. Results of this study later showed a positive relationship between social support and adjustment , with r = 0.545 , significance level of 5 % , which means the relationship between independent variables ( X2 ) with the dependent variable ( Y ) strong and significant . Results of this research later showed a positive relationship between social support and adjustment, with r = 0.597 significance level of 5 % , which means the relationship between independent variables ( X1 , X2 ) with the dependent variable ( Y ) strong and significant. Donations were given self-efficacy of 19.5 %, amounting to 29.7 % of social support and simultaneously self-efficacy and social support contributed by 35.6 % to a variable of adjustment